2016
DOI: 10.1002/jsfa.7677
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of oxidation parameters of purified Kilka fish oil including gallic acid and methyl gallate by adaptive neuro‐fuzzy inference system (ANFIS) and artificial neural network

Abstract: Sensitivity analysis based on the ANFIS model suggested a high sensitivity of oxidation parameters, particularly the induction period on concentrations of gallic acid and methyl gallate due to their high antioxidant activity to retard oil oxidation and enhanced Kilka oil shelf life. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…We therefore suggest applying the ANFIS model with generalized bell MFs to predict the oxidative stability of VOO. Similar results were found in studies conducted by several groups of scientists, applying artificial ANFIS to model the edible oil industry, for instance, Prediction impact of curcumin on soybean oil with a correlation coefficient (R 2 ≥ 0.98), prediction of rapeseeds oil extraction with a correlation coefficient (R 2 ≥ 0.998), fatty acid profile of vegetable oils based on rheological analysis with correlation coefficient (R 2 ≥ 0.995), effect of natural antioxidant added on hazelnut oil oxidation with correlation coefficient (R 2 ≥ 0.996), oxidation state of purified kilka fish oil with correlation coefficient (R 2 ≥ 0.993) …”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We therefore suggest applying the ANFIS model with generalized bell MFs to predict the oxidative stability of VOO. Similar results were found in studies conducted by several groups of scientists, applying artificial ANFIS to model the edible oil industry, for instance, Prediction impact of curcumin on soybean oil with a correlation coefficient (R 2 ≥ 0.98), prediction of rapeseeds oil extraction with a correlation coefficient (R 2 ≥ 0.998), fatty acid profile of vegetable oils based on rheological analysis with correlation coefficient (R 2 ≥ 0.995), effect of natural antioxidant added on hazelnut oil oxidation with correlation coefficient (R 2 ≥ 0.996), oxidation state of purified kilka fish oil with correlation coefficient (R 2 ≥ 0.993) …”
Section: Resultssupporting
confidence: 84%
“…The application of the ANFIS in food science has been reported by several researchers in the field. It was used to predict the fatty acid profiles of vegetable oils, in rapeseed oil extraction, and for estimating the effect of antioxidant activity on hazelnut oil oxidation, and the oxidation behavior of purified kilka fish oil …”
Section: Introductionmentioning
confidence: 99%
“…The PV (meqO 2 /kg oil) of sunflower oil samples containing different concentrations of lemon verbena essential oil and BHT was measured spectrophotometrically at 500 nm by UV‐VIS instrument (model 160A Shimadzu, Tokyo, Japan). The oil samples were mixed in with 9.8 ml chloroform–methanol (7:3 v/v) on a vortex mixer for 2–4 s. Ammonium thiocyanate solution (50 ml, 30% w/v) and 50 ml of iron (II) chloride solution ([0.4 g barium chloride dihydrate dissolved in 50 ml H 2 O] + [0.5 g FeSO 4 ·7H 2 O dissolved in 50 ml H 2 O] + 2 ml 10 mol/L HCl, with the precipitate, barium sulfate, filtered off to produce a clear solution]) were added, respectively, and after adding each of them, the sample was mixed on a vortex mixer for 2–4 s. Then, the absorbance of the sample was read, after 5 min incubation at room temperature (Asnaashari, Farhoosh, & Farahmandfar, ).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have reported that these harmful effects can be reduced by regular consumption of foods and beverages which exhibit antioxidant activity (Farhoosh, Sharif, Asnaashari, Johnny, & Molaahmadibahraseman, ). Moreover, medicinal plants play a crucial role to cure basic health problems (Asnaashari, Farhoosh, & Farahmandfar, ). So, try to achieve new natural antioxidative and antimicrobial compounds due to a people tendency to consumption of food without chemical preservatives has been increasing.…”
Section: Introductionmentioning
confidence: 99%